Evidence of the Involvement of Spinal EZH2 in the Development of Bone Cancer Pain in Rats - Chen H (Dove Medical Press, 2021)
Haoming Chen,* Jianmang Yu,* Lihua Hang,* Shuai Li, Weikang Lu, Zhenkai Xu Department of Anesthesiology, Kunshan First People’s Hospital Affiliated to Jiangsu University, Kunshan, Jiangsu, 215300, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lihua HangDepartment of Anesthesiology, Kunshan First People’s Hospital Affiliated to Jiangsu University, Suzhou, Jiangsu Province, Peoples Republic of ChinaTel +86-18013273169Email zjhanglihua@foxmail.comIntroduction: Bone cancer pain (BCP) seriously affects the quality of life of patients with advanced cancer, but effective treatment methods are lacking. This study mainly investigates the role of EZH2 in a well-established BCP model induced by Walker 256 breast cancer cells in rats.Methods: Female Sprague–Dawley rats of the same age weighing approximately 160 g were selected for the experiment. The BCP model was established by injecting inactivated Walker 256 breast cancer cells into the tibia. von Frey filaments were used to measure the paw withdrawal threshold, and bone destruction in the rat was observed using x-ray. The spinal EZH2 and H3K27Tm levels were measured using Western blotting and RT–qPCR analysis. Intrathecal injection of an EZH2 inhibitor was performed to examine the role of EZH2 in trigeminal BCP.Results: Experimental results showed that injecting Walker 256 breast cancer cells into the tibia induced bone cancer pain. Spinal EZH2 and H3K27Tm levels were significantly increased over time in BCP rats. An intrathecal injection of 3-deazaneplanocin A (DZNep), a selective EZH2 inhibitor, downregulated the expression of EZH2 and attenuate the BCP-induced mechanical allodynia state.Conclusion: Intrathecal injection of DZNep relieve bone cancer pain in rats. EZH2 expressed in spinal cord tissue may be involved in the process of bone cancer pain in rats.Keywords: enhancer of zeste homologue 2, bone cancer pain, histone methyltransferase, 3 deazaneplanocin A, intrathecal injection